2012
DOI: 10.1007/s10995-012-1158-9
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Gestational Weight Gain Counseling and Tracking

Abstract: Objectives Excessive gestational weight gain (GWG) predicts adverse pregnancy outcomes and later obesity risk for both mother and child. Women who receive GWG advice from their obstetric clinicians are more likely to gain the recommended amount, but many clinicians do not counsel their patients on GWG, pointing to the need for new strategies. Electronic medical records (EMRs) are a useful tool for tracking weight and supporting guideline-concordant care, but their use for care related to GWG has not been evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Health professionals in the United Kingdom also promoted the concept of group sessions that had an emphasis on behavioral change techniques and were previously piloted as part of a feasibility study of an “antenatal lifestyle course” for women with a BMI≥30 kg/m 2 . (57) The need for groups was partially attributed to the multi-factorial nature of obesity which requires an integration of health care services, similar to the multidisciplinary approach providers in the current study suggested as well.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Health professionals in the United Kingdom also promoted the concept of group sessions that had an emphasis on behavioral change techniques and were previously piloted as part of a feasibility study of an “antenatal lifestyle course” for women with a BMI≥30 kg/m 2 . (57) The need for groups was partially attributed to the multi-factorial nature of obesity which requires an integration of health care services, similar to the multidisciplinary approach providers in the current study suggested as well.…”
Section: Discussionsupporting
confidence: 68%
“…Communication skills are critical given that prenatal care providers have difficulty in discussing this topic (e.g., “…have to choose our words carefully”). (57) This concept also extends to the psychological aspects of being obese and pregnant and addressing mental health problems such as depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,19,20 In studies of providers' knowledge and attitude of GWG, few providers know and recommend the appropriate weight gain range concordant with IOM guidelines. [21][22][23] Information regarding knowledge and beliefs about GWG among Spanish-speaking women is limited. Several studies have demonstrated that Hispanic women gain more weight than nonHispanic women during pregnancy, 24-26 the reasons for which are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…da equipe de saúde; c) problemas organizacionais para oferecer o controle pré-natal 40 ; d) barreiras do tipo social e/ou cultural 41 ; e) dificuldades de acesso geográfico ao serviço 42 ; f) ausência de credibilidade nos benefícios oferecidos pelo sistema de saúde e na necessidade de controle da gestação; g) falta de promoção do serviço nas comunidades e de aceitação da sua importância 43 . Para que esses obstáculos sejam superados, é necessário que a organização dos cuidados pré-natais contemple, no mínimo, a garantia de: a) captação precoce da gestante na comunidade; b) atendimento periódico contínuo e extensivo à população-alvo; c) provisão de recursos humanos técnico e cientificamente preparados 44 ; d) área física adequada; e) provisão de equipamentos e instrumentais adequados; f) realização de exames laboratoriais obrigatórios; g) abastecimento e acesso aos medicamentos básicos; h) sistema eficiente de referência e contra referência; i) serviço de registro e de estatística 45 ; j) sistema de avaliação da efetividade das ações de assistência pré-natal 10,33 . O envolvimento da comunidade e dos profissionais integrantes da equipe de saúde é essencial para a captação precoce das gestantes, permitindo que ações de prevenção e tratamento sejam introduzidas oportunamente.…”
Section: Resultsunclassified